Social and behavioral risk factors associated with cognitive impairment among the middle-aged and elderly Russian population - A. E. Imaeva; A. V. Kapustina; V. A. Kutsenko; Yu. A. Balanova; S. A. Maksimov; G. A. Muromtseva; M. B. Kotova; N. S. Karamnova; S. E. Evstifeeva; O. A. Litinskaya; M. S. Pokrovskaya; N. A. Imaeva; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To assess the associations of social and behavioral risk factors with cognitive impairment in the Russian population aged 55-74 years.Material and methods. This study was conducted as part of the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation-3 (ESSE-RF3) study. A total of 13736 participants living in 14 Russian regions were examined. Cognition was assessed using the Mini-Mental State Examination (MMSE) score as follows: cognitive impairment was recorded in the total score<24, based on 30 points. Associations were assessed using logistic regression after adjusting for sociodemographic characteristics, drinking status, and the presence of hypertension and stroke.Results. According to the multivariate analysis, no higher education (odds ratio (OR) 2,5 (95% confidence interval (CI): 1,98-3,27), p=0,001), no marriage (OR 1,6 (95% CI: 1,29-2,00), p=0,001), unemployment (OR 2,2 (95% CI: 1,71-2,86), p=0,001), and low income (OR 2,04 (95% CI: 1,60-2,57), p=0,001) are significantly associated with cognitive impairment. Of the 4 behavioral risk factors studied, only insufficient consumption of vegetables and fruits was significantly associated with cognitive impairment (OR 1,52 (95% CI: 1,18-1,99), p=0,001)Conclusion. The study results indicate an association between cognitive impairment and education, marital status, income, employment, professional activity, as well as insufficient consumption of vegetables and fruits.